Full utilization of sweet sorghum for biofuel production - Appiah-Nkansah, Nana Baah (Kansas State University, 2017)
Sweet sorghum accumulates high concentrations of fermentable sugars in the stem, produces significant amount of starch in the grain (panicle) and has shown to be a promising energy feedstock. Sweet sorghum has a short growing season so adding it to the sugar cane system would be good. The overall goal of this dissertation is to enhance the attractiveness of biofuel production from sweet sorghum to fully utilize fermentable sugars in the juice, starch in the panicle and structural carbohydrates in the stalk for high efficiency and low-cost ethanol production. Sweet sorghum juice was incorporated into the dry-grind process which achieved 28% increase of ethanol yield compared to the conventional ethanol method and decreased enzymatic hydrolysis time by 30 minutes. A very high gravity fermentation technique was applied using sweet sorghum juice and sorghum grain yielded 20.25% (v/v) of ethanol and 96% fermentation efficiency. Response surface methodology was applied in order to optimize diffusion conditions and to explore effects of diffusion time, diffusion temperature, and ratio of sweet sorghum biomass to grain on starch-to-sugar efficiency and total sugar recovery from sweet sorghum. Starch hydrolysis efficiency and sugar recovery efficiency of 96 and 98.5% were achieved, respectively, at an optimized diffusion condition of 115 minutes, 95 °C, and 22% grain loading. Extraction kinetics based on the optimized diffusion parameters were developed to describe the mass transfer of sugars in sweet sorghum biomass during the diffusion process. Ethanol obtained from fermented extracted sugars treated with granular starch hydrolyzing enzyme and those with traditional enzymes were comparable (14.5 – 14.6% v/v). Ethanol efficiencies also ranged from 88.92 –92.02%.
Keywords: Sweet sorghum; Fermentation; Diffusion process; Dry-grind ethanol process; Bioenergy and biofuels; Mass transfer kinetics